The Impact of Social Hierarchies on Efforts at Organizational Change: Comparing Two Approaches from the Tavistock Institute for Human Relations. (23rd September 2013) - Rudden, Marie; Lazes, Peter; Neumann, Jean
ABSTRACT: Two approaches to organizational consultation – psychodynamic systems and socio‐technical systems theories – originally developed at the Tavistock Institute for Human Relations but diverged several decades ago. We describe each approach and analyze its effectiveness in a community consultation in which the presence of social hierarchies presented a considerable challenge. We then discuss a consultation in which both approaches were combined, and argue for the benefits of this joint technique. Copyright © 2013 John Wiley & Sons, Ltd.